The Nature of Second-hand Camera Store Business (The Indonesian Journal of Business Administration, 2021)
In 2008 there were already researchers that studying the second-hand markets, they research customer motivation in general towards second-hand shopping in UK, taking flea market and garage sale as their research subjects. This study tries to be a continuation of previous research where this study more focusing on second-hand camera store subject. The difference between previous subject is that flea market and garage sale tend to be more personal and less competitive, while second-hand camera store are more business like. This study sheds light on how socio-cultural issue could derive different motives towards second-hand camera shopping, while the nature of the business itself in today era makes this business less attractive yet the market is there by answering the question: how to do a proper second-hand camera businesses?. This study conducted a single-case study in unit business from well known brand of second-hand camera store in Indonesia to analyze the nature of second-hand camera store business. The data pertaining to second-hand camera store business in Indonesia are collected through questionnaire and supported by theory and expertise interviews. The results of this study is the addition of an element of trust as an aspect of people’s motivation towards second-hand shopping camera, and provides new insight into theoretical issue on how to analyze competitor in current condition where e-commerce already become parts of daily life, smart phone and rental camera business are becomes camera substitute that are more affordable, and Covid-19 pandemic is forcing people to stay at home. Key Words: Second-hand Camera Store, Marketing Mix Strategy, Porter’s Generic Strategy, TOWS Matrix.